Review: Course in structural engineering. Regional Center for Technological Developments for Construction, Seismology and Seismic Engineering CEDERETEC (Gaceta Técnica, 2020)
This is the review of the Structural Engineering Update course carried out at the Regional Center for Technological Developments for Seismology and Seismic Engineering Construction (CeDeReTec, Mendoza, Argentina) at the end of the year 2019. The presentations are shown and also reports on the activities carried out within the framework of the Project “Destructive Potential Generated by the Earthquake of Ecuador of April 16, 2016” are reported.
Keywords: steel design; seismic dissipation; dynamic response